The Role of Village-Owned Enterprises (Bumdes) in Managing Prime Educational Tourism Selemak, Hamparan Perak North Sumatera - Sinaga, Caroline; Simanjuntak, Anggraini Oktaviani Pauline; Ginting, Arca Iswari Br; Napitupulu, Inda Triwana (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
Prima Wisata Edukasi Selemak is an educational destination that is very suitable to be used as a place to relax. Prima Wisata Edukasi Selemak is located on Ustad. H. Abdul Khadir Nuh, Kelumpang, Kec. Hamparan Perak, Kab. Deli Serdang, North Sumatra 20256. This study aims to determine the role of BUMDes in the governance of Prima Selemak Educational Tourism and to analyze the role of BUMDes in managing Selemak Educational Tourism, Hamparan Perak. To find out the government's contribution to BUMDes in increasing the management revenue of Prima Wisata Edukasi Selemak. This research uses qualitative methods obtained through visits to Prima Wisata Edukasi Selemak. It uses data collection methods through in-depth interview observations with BUMDes administrators or managers based on informants who are one of the BUMDes sections and are also of the village officials of Prima Wisata Edukasi Selemak. In general, this research can provide information related to BUMDes in the management of Selemak Village. Prima Wisata Edukasi Selemak is assisted by BUMDes in managing this tourism business so that the results are by the previously compiled process. BUMDes focuses on addressing this Village by providing services in the field of promotion in the introduction of these tourism businesses. The results of the discussion of this research are some of the roles of BUMDes in the governance and development of the Selemak Prima Edukasi Tourism Park, namely, as a driver and as a reference in bringing high multiplier effects to local communities, and also plays a role in the development, empowerment and development of the community in the Village. The government has yet to contribute to increasing revenue at Taman Wisata Edukasi Selemak. Still, in providing education to local communities, the government has taken part and promoted Taman Wisata Edukasi Selemak.